2015
DOI: 10.1371/journal.pone.0117342
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing of Codonopsis pilosula and Identification of Candidate Genes Involved in Polysaccharide Biosynthesis

Abstract: Background Codonopsis pilosula (Franch.) Nannf. is one of the most widely used medicinal plants. Although chemical and pharmacological studies have shown that codonopsis polysaccharides (CPPs) are bioactive compounds and that their composition is variable, their biosynthetic pathways remain largely unknown. Next-generation sequencing is an efficient and high-throughput technique that allows the identification of candidate genes involved in secondary metabolism.Principal FindingsTo identify the components invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…The sequencing produced 193,032,910 clean reads and 53,544 unigenes after assembly. The number of unigenes obtained from P. ternata was lower than that obtained from Carthamus tinctorius (120,778) (Lulin et al, 2012), Polygonum cuspidatum (86,418) (Hao et al, 2012), and Salvia miltiorrhiza (64,139) , However, the number of unigenes obtained from P. ternata was higher than that from Codonopsis pilosula (45,511) (Gao et al, 2015), and Isatis indigotica (36,367) (Chen et al, 2013). The average unigene length (611 bp) was slightly greater than that of other medicinal plants, including C. tinctorius (446 bp) (Lulin et al, 2012), S. miltiorrhiza (413 bp) , and P. cuspidatum (365 bp) (Hao et al, 2012).…”
Section: Ssr Discoverymentioning
confidence: 85%
“…The sequencing produced 193,032,910 clean reads and 53,544 unigenes after assembly. The number of unigenes obtained from P. ternata was lower than that obtained from Carthamus tinctorius (120,778) (Lulin et al, 2012), Polygonum cuspidatum (86,418) (Hao et al, 2012), and Salvia miltiorrhiza (64,139) , However, the number of unigenes obtained from P. ternata was higher than that from Codonopsis pilosula (45,511) (Gao et al, 2015), and Isatis indigotica (36,367) (Chen et al, 2013). The average unigene length (611 bp) was slightly greater than that of other medicinal plants, including C. tinctorius (446 bp) (Lulin et al, 2012), S. miltiorrhiza (413 bp) , and P. cuspidatum (365 bp) (Hao et al, 2012).…”
Section: Ssr Discoverymentioning
confidence: 85%
“…In general, polysaccharide ingredients are known for their activity in strengthening the human body’s immunity, i.e., ganoderma polysaccharides and ginseng polysaccharides. In addition, codonopsis polysaccharides (CPPs) are capable of preventing tumor growth, improving memory, curing diabetes, and increasing hemoglobin [24]. Yang et al [44] demonstrated that CPPs are an acidic hetero-polysaccharide composed of arabinose, glucose, rhamnose, galactose, mannose, glucuronic acid, and galacturonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…are traditionally used in Chinese medicine for replenishing qi (vital energy) deficiency, strengthening the immune system, improving poor gastrointestinal function, curing gastric ulcers, and appetite [21]. The bioactive constituents are mainly composed of alkaloids [22], phenylpropanoids, polyacetylenes [23], polysaccharides [24], and terpenoids [25]. Lobetyolinin and lobetyolin, which is effective in protecting the gastric mucosa, are the major ingredients of polyacetylenes in C. pilosula [26], while the most common terpenoid is atractylenolide III, which has anti-inflammatory activity [27].…”
Section: Introductionmentioning
confidence: 99%
“…Raphanus sativus (773bp) [45], Camelia sinensis (521bp) [47] and Codonopsis pilosula (1,243bp) [48] infers fairly good assembly of transcriptome of the study. We predicted, 26569, 18605, 28588 and 22599 CDS respectively in SI, SU, RI and RU of Isabgol transcriptome of which more than 90% have blast hits in 'nr' database of NCBI which is comparatively higher than reported in Isabgol [34] and grapes [23][24] and pearl millet [27].…”
Section: Realtime Gene Expression Analysismentioning
confidence: 66%